Libertà di pensiero nell’era digitale. Genesi ed evoluzione della libertà di pensiero dal V sec. a.C. ad oggi: sfide, rischi e prospettive future - Marsili, M. (2025)
The freedom to express one's thoughts is recognized by all modern democratic constitutions, enshrined in the Universal Declaration of Human Rights of 1948, the European Convention of 1950, and the International Covenant of New York of 1966. Its establishment is the result of a journey that began in 5th-century BC Greece (with the opposition between nomos and physis), passing through the French Revolution and the Napoleonic era, up to parliamentary democracies, which have consecrated freedom of opinion and the press among fundamental rights. Published in a first edition by Mimesis in 2011, the volume has now been revised and expanded, intertwining historical-philosophical analysis and critical reflection on the impact of digital technologies. It addresses crucial issues such as privacy, disinformation, cognitive manipulation, content moderation, and surveillance capitalism, showing how freedom of thought is constantly redefined in the digital environment, amid risks of censorship, fake news, and the concentration of informational power. With an eye to the future, the work proposes tools and perspectives for a global and sustainable governance of digital freedom, offering readers essential keys to understanding and addressing the transformations of an interconnected society.